The Effect of Realistic Mathematics Education Learning Models on The Learning Outcomes of Exponential Functions And Logarithmic Functions: The Effect of Realistic Mathematics Education Learning Models on The Learning Outcomes of Exponential Functions And Logarithmic Functions - supriyanto (Journal of diversity in learning (JDIL), 2020)
The purpose of this research is to know: (1) Management of learning by teachers,(2) Student activities in the learning process and (3) The completeness of student learning outcomes. This study's subjects were students of grade X MIA-6 of SMAN 1 Ngimbang school year 2018-2019, which numbered 35 students. The research design used is Class Action Research (PTK). Analisis data of the research results can be concluded that: (1) The ability of teachers in managing constructivist learning with RME (2)Teacher activity during learning during three cycles generally increases - Katan, in cycle I to cycle there is an increase, (3) Student activity during three cycles, in general, has increased, and (4) Classical completion of student learning in the cycle to cycle II increases to and in cycle III decreases, the student's response has good response with the number of students who answer the RME application.